If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 2q = 3p + -3q Solving 5p + 2q = 3p + -3q Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. 5p + -3p + 2q = 3p + -3p + -3q Combine like terms: 5p + -3p = 2p 2p + 2q = 3p + -3p + -3q Combine like terms: 3p + -3p = 0 2p + 2q = 0 + -3q 2p + 2q = -3q Add '-2q' to each side of the equation. 2p + 2q + -2q = -3q + -2q Combine like terms: 2q + -2q = 0 2p + 0 = -3q + -2q 2p = -3q + -2q Combine like terms: -3q + -2q = -5q 2p = -5q Divide each side by '2'. p = -2.5q Simplifying p = -2.5q
| 7j+14=98 | | (3x)2+(2x)2=117 | | 5t-4=3f+6 | | 6(k+8)=90 | | 2(w+11)=40 | | 10(u+7)=80 | | x^2-2x-16=x^2 | | 0=-3x^2+24x-36 | | 6(g-91)=6 | | 3q+21=72 | | 2+6u=44 | | 6=167+21 | | 2x+-2=11x-38 | | (x+2)(x+3)=(3x+4)(x+3) | | 1.1x*0.583=0.2 | | 10y+13x+200=1500 | | 25=4y+29 | | x-3(2x+8)=-3 | | 0.2=x+(x-0.1)*0.583 | | x-6x+8=-3 | | 4(3x-y)=40 | | 5(2x-3)=2(5x+3) | | 6(x+2)=2x+2(x+1) | | 4x-(3-5x)=87 | | .65x=5 | | (9x+9)+(14x-6)=90 | | -3x+2=3(4+-x) | | (8)x(-5)= | | x*5=11.2-x | | 12t-5=8t+13 | | 40=10x+5y | | 0.03r^2+r=0 |